Rent-seeking versus Productive Activities in a Multi-task Experiment - Hessel Oosterbeek; Randolph Sloof; Joep Sonnemans (Tinbergen Institute, 2006)
Incentive instruments like asset ownership and performance pay often have to strike a balance between the productive incentives and the rent-seeking incentives they provide. Standard theory predicts that a given instrument becomes less attractive when the effectiveness of rent-seeking activities increases. More recent theories that emphasize the importance of reciprocity, however, suggest that this relationship may go the other way around. In this paper we test these predictions by means of a laboratory experiment. By and large our findings confirm standard theory. Incentive instruments typically become less attractive when the scope for rent-seeking activities increases. However, reciprocity motivations do seem to mitigate the adverse effects of rent-seeking opportunities to a considerable extent.
Keywords: C91; M52; 330; multi-task experiment; rent-seeking; reciprocity; Rent-Seeking; Austauschtheorie (Soziologie); Test